Faunistical and Ecological Studies on Carabid Beetles - Magura, Tibor (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this paper on the distribution of carabids at high altitudes, the effect of Nature 2000 habitat and landform types in driving ground beetle (Carabidae) distribution at high altitudes in the Western Dolomites (Brenta group, Italy) was studied. Papers studying carabid beetles in forested habitats investigated the effect of different stand composition (pure oak stands, oak-pine mixed stands, single tree admixtures of oak in pine stands, and pure pine stands) on the abundance and spatial distribution of large-sized Carabus species, as well as the effect of forest type (broad-leaved deciduous forests vs. coniferous plantations) on the diversity and community composition of ground beetles; furthermore, the effect of various forest edges (natural vs. anthropogenic edges) on the abundance of ground beetles of different habitat affinity and dispersal power was examined. The paper on predation pressure aimed to explore the predation pressure on carabids using 3D-printed decoys installed in two types of forestry treatments, preparation cuts and clear cuts, and control plots in an oak-hornbeam forest.